Implementation of vibration feedback in a motion based driving simulator - Arvidsson, Gabriel; Patel, Edward (My University, 2026)
Driving simulators are efficient tools for research. However, traditional moving-base platforms have limited ability to reproduce high-frequency vibrations. As a result, the simulation may feel less realistic and lead to increased sensory mismatch. This thesis presents the implementation of a haptic seat actuator in the SimIV driving simulator at the Swedish National Road and Transport Research Institute (VTI), with the aim of strengthening the driver’s perception of realistic vehicle motion. Field measurements were carried out using both internal combustion engine and electric vehicle to try to isolate road and engine-induced vibrations across various speeds. Frequency analysis revealed several characteristics including wheel resonance, longitudinal back and forth body motion, tyre structural modes, and engine harmonics. A bass shaker (Xcite XBS100-4) was welded onto a plate beneath the simulator seat. A Python algorithm was developed to process live simulator telemetry via UDP. The algorithm continuously blends several vibration sources together, road noise, engine vibration, braking feedback and simulated rumble strips. A small user validation study suggested that the integration of the haptic vibrations improved the perceived realism of the simulator, the subjective connection to the road, and strengthened the physical feedback of vehicle speed and acceleration.
Keywords: Sim IV; motion-cueing; haptic feedback; vibrations; simulation; simulator; driving simulator